Islamic Family Financial Management - Hartato Rianto; Hastuti Olivia; Saparuddin Siregar (Proceeding International Seminar of Islamic Studies, 2019)
Thestretching of theIslamiceconomyin Indonesia is still very concerning.Theenormousquantity ofMuslimcommunitiesin Indonesia has not been matched by quality in terms of the Islamic economy.The quality of Indonesian society is low in terms of the Islamic economy due to the low level of literacy that the community has.This confirms that the study ofIslamiceconomicsthat has been carried out has not been conveyed to the public as a whole.This study examines the management of Islamic family finances, so that theMuslimcommunityin Indonesia can better understand the management of money held in accordance with Islamic law.This study uses secondary data that is systematically analyzed to examine financial management that can be done by households based on the Koran and hadiths.The results of this study explain that households must pay attention to the halal of incoming and outgoing money.Consumption must be brought to the maslaha, and prioritize investment behavior in accordance withIslamiclawcompared with saving behavior.